THE ROLE OF BAZNAS IN EMPOWERING EDUCATION IN CENTRAL TAPANULI DISTRICT - Gulo, Kamil; Budianti, Yusnaili; Hanum, Azizah (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
This study aims to analyze the role of BAZNAS in empowering the people in Central Tapanuli Regency including social and educational conditions, programs, implementation, and obstacles in Central Tapanuli BAZNAS. The type of research uses qualitative, data collection techniques with observation, interviews, and documentation. The data analysis technique in this study uses reduction, data presentation, and conclusion drawn. The results of the study include the first four points; The role of the National Amil Zakat Agency on the welfare of the community refers to Government Regulation of the Republic of Indonesia Number 14 of 2014 concerning the implementation of Law Number 23 of 2011 concerning Zakat Management. Second; There are five programs distributed by BAZNAS Central Tapanuli Regency, smart Central Tapanuli Regency program, Central Tapanuli Taqwa Regency program healthy Central Tapanuli Regency program, Central Tapanuli Makmur Regency program, Central Tapanuli Regency care program. Third; The role of BAZNAS of Central Tapanuli Regency has played a role in the implementation of the program, and fourth; the obstacles in distributing zakat funds also have obstacles but are not so serious that there are solutions for each.